Corporate Social Responsibility as a tool to ensure sustainability and competitiveness of the monotowns; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Sechina A. A. Asya Aleksandrovna; Fedenkova A. S. Anna Sergeevna; Pokrovskaya N. Natalia; Kropova A. Alena (2016, 2016)
Title screen